Beyond The Checkbox: Development And Validation Of A Scale Measuring MBBS Students’ Attitudes, Barriers, And Preferences Toward Academic And Clinical Documentation - Revathi Krishnakumar; Anbarasi Muthusamy; Rajkumar Gajendran (Adolescência e Saúde, 2026)
Background: Competency-Based Medical Education (CBME) in India relies on assignments, Self-Directed Learning (SDL) record book entries, and clinical logbook documentation as core mechanisms for developing self-regulated, lifelong learners. Prior survey work suggests these elements are inconsistently well received by MBBS students, yet no validated, multi-domain instrument exists to assess attitudes, perceived barriers, and preferences across all three tasks within a single framework, nor to link self-report data with objective compliance records. Objective: To develop and psychometrically validate the Attitude, Barriers, and Preferences towards Academic and Clinical Documentation Scale (AACDS), including an item assessing preference for extending the National Medical Commission’s (NMC) postgraduate e-logbook mandate to undergraduate level. Methods: The 48-item AACDS (40 Likert-scaled attitude/barrier items across four subscales, plus 8 preference/opportunity items) was evaluated across six validation strands: content validity (10-expert panel), face validity (pilot, n=15), internal consistency reliability (pilot, n=35), exploratory factor analysis (n=300), test–retest reliability (n=50, 2-week interval), and inter-rater reliability of a linked objective Entry Quality Rubric (2 raters, 20 entries). Results: Content validity was excellent (S-CVI/Ave = 0.902; all 48 items I-CVI ≥ 0.78). Face validity was strong (mean clarity = 87.8%; 0/48 items flagged). Internal consistency was acceptable to good across subscales (α = 0.783–0.824). Exploratory factor analysis (KMO = 0.85; Bartlett's χ²(435) = 2217.67, p < .001) supported by parallel analysis confirmed the hypothesized three-factor structure (Assignments, SDL Record Book, Clinical Logbook) with small cross-loadings (< .15 in magnitude), explaining 37.68% of variance. Test–retest reliability was good (ICC = 0.78). Inter-rater reliability for the objective Entry Quality Rubric was almost perfect (pooled κ = 0.90; ICC = 0.88). Conclusion: The AACDS's 40-item attitude/barrier core demonstrates robust, multi-method psychometric validation for assessing MBBS students' engagement with CBME documentation requirements; validation of the 8 Section E preference items remains pending. It is, to our knowledge, the first instrument to jointly capture attitudes, barriers, and preferences across assignments, SDL, and logbook documentation while linking self-report data to objective institutional records, positioning it as a practical tool for curriculum evaluation and for informing undergraduate digital documentation policy.